Green extraction of total phenolic and flavonoid contents from mangosteen (Garcinia mangostana L) rind using natural deep eutectic solvents. Issue 4 (April 2023) - Vo, Tan Phat; Pham, Ngoc Duyen; Pham, Thuy Vy; Nguyen, Hoang Yen; Vo, Le Thao Vy; Tran, Thi Ngoc Huyen; Tran, Tri Nguyen; Nguyen, Dinh Quan
Abstract: This research combined ultrasonic-assisted extraction (UAE) and natural deep eutectic solvent (NADES) to recover phenolic and flavonoid components from mangosteen rind. The antioxidant activities were determined using DPPH, ABTS +, and hydroxyl assays. NADES prepared from lactic and 1, 2–propanediol had the highest extraction efficiency based on the total flavonoid content (TFC) and phenolic contents (TPC). Single-factor experiments were employed to assess the influence of UAE conditions (liquid-to-solid ratio, temperature, water content in NADES, and time) on TFC, TPC, and antioxidant activities. NADES-based UAE conditions were optimized using response surface methodology with the Box-Behnken design model on five dependent responses (TPC, TFC, DPPH, ABTS, and OH). The optimal conditions for the lactic-1, 2–Propanediol-based UAE process were 76.7 ml liquid/g solid with 30.3% of water content at 57.5 °C for 9.1 min. Scanning electron microscopy (SEM) was applied to examine the surface morphology of mangosteen rind before and after sonication. This study proposes an efficient, green, and practical approach for recovering phenolics and flavonoids from mangosteen rinds. Graphical abstract: Image 1